2008
DOI: 10.1186/1471-2407-8-125
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TRPC6 channels in human epithelial breast cancer cells

Abstract: Background: TRP channels have been shown to be involved in tumour generation and malignant growth. However, the expression of these channels in breast cancer remains unclear. Here we studied the expression and function of endogenous TRPC6 channels in a breast cancer cell line (MCF-7), a human breast cancer epithelial primary culture (hBCE) and in normal and tumour breast tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 39 publications
2
54
1
2
Order By: Relevance
“…However, our data showed that only TRPC6 was selectively increased in response to nicotine, while the other subtypes TRPC1/3/4 did not change in HBSMCs. Interestingly this finding differs from a previous study reporting that TRPC6 alone induced OAG-activated calcium influx in human epithelial breast cancer cells [49]. It also differs from our previous study reporting that the enhanced ROCE due to upregulated TRPC6 is a novel pathogenic mechanism contributing to the increased basal [Ca 2+ ] i in pulmonary venous smooth muscle cells (PVSMC) and excessive PVSMC proliferation during the development of hypoxic pulmonary hypertension [50].…”
Section: Discussioncontrasting
confidence: 55%
“…However, our data showed that only TRPC6 was selectively increased in response to nicotine, while the other subtypes TRPC1/3/4 did not change in HBSMCs. Interestingly this finding differs from a previous study reporting that TRPC6 alone induced OAG-activated calcium influx in human epithelial breast cancer cells [49]. It also differs from our previous study reporting that the enhanced ROCE due to upregulated TRPC6 is a novel pathogenic mechanism contributing to the increased basal [Ca 2+ ] i in pulmonary venous smooth muscle cells (PVSMC) and excessive PVSMC proliferation during the development of hypoxic pulmonary hypertension [50].…”
Section: Discussioncontrasting
confidence: 55%
“…We have previously demonstrated that TRPC6 and TRPM7 are overexpressed in hBDA at both protein and mRNA levels, and their functional expression was recorded in the MCF-7 cancer cell line and human breast cancer epithelial (hBCE) cells isolated from surgical resection [29,30]. We also reported that TRPM8 expression is regulated by estrogens in breast cancer cells and tissues [31].…”
Section: Introductionmentioning
confidence: 97%
“…Through a phospholipase C (PLC)-dependent mechanism, they can be activated by G-protein coupled receptors or receptor tyrosine kinases [7]. Recently, it has been shown that TRPC6 contributes to the proliferation of some types of cancer cells [8][9][10]. In addition, in the primary human prostate cancer epithelial (hPCE) cells and LNCaP cells, agonist-mediated stimulation of α 1 -adrenergic receptors requires the coupled activation of TRPC6 channels and nuclear factors of activated T cells to promote cell proliferation [11,12].…”
Section: Introductionmentioning
confidence: 99%